Peran Kebijakan Keamanan dalam Mengurangi Unauthrized Access pada Sistem Informasi - Saputra, Rivki; Icwan, Muhamad Rizky; Wardani, Yuga Tama; Asandi, Angjela Putri; Agustina, Titin (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
Unauthorized access to information systems is a major challenge for organizations in the digital era. This journal discusses the role of security policies in mitigating such risks through literature review, risk analysis, and implementation evaluation. The research shows that comprehensive security policies, including data encryption, two-factor authentication, and system monitoring, are effective in protecting digital assets. Risk management and staff education also play an important role in improving security. In conclusion, investment in security infrastructure and staff training are essential to maintain data integrity and prevent